The Role of Herbal Plant Essential Oils in the Treatment of Acne Vulgaris - Kelvin; Linda Julianti Wijayadi (Science Midwifery, 2022)
Acne vulgaris (AV) is a disease of the pilosebaceous unit that often occurs at the age of 15 to 40 years. Various factors can influence this disease such as abnormal keratinization, microbial colonization, increased sebum production and complex inflammatory mechanisms. Essential oils can be used as an alternative therapy for AV. Various kinds of essential oils which are natural aromatic compounds from herbal plants, have long been known to help cure AV. This is because of the various beneficial compounds contained in each essential oils. The effects are varied such as anti-inflammatory, antioxidant and antimicrobial which will affect the healing mechanism of AV. This literature review discusses the role of essential oils from kaffir lime (Citrus hystrix), cinnamon (Cinnamomum), tea tree (Melaleuca alternifolia), lemongrass (Cymbopogon citratus (DC) Stapf. and Cymbopogon flexuosus), oregano (Origanum vulgare) and lavender (Lavandula angustifolia) against AV treatment.